Targeting c-Met in breast cancer: From mechanisms of chemoresistance to novel therapeutic strategies - Emeka Eze Joshua Iweala; Doris Nnenna Amuji; Abimbola Mary Oluwajembola; Eziuche Amadike Ugbogu (Current Research in Pharmacology and Drug Discovery)
Breast cancer presents a significant challenge due to its heterogeneity and propensity for developing chemoresistance, particularly in the triple-negative subtype. c-Mesenchymal epithelial transition factor (c-Met), a receptor tyrosine kinase, presents a promising target for breast cancer therapy due to its involvement in disease progression and poor prognosis. However, the heterogeneous expression of c-Met within breast cancer subtypes and individual tumors complicates targeted therapy. Also, cancer cells can develop resistance to c-Met inhibitors through various mechanisms, including bypass signaling pathways and genetic mutations. The off-target effects of c-Met inhibitors further limit their clinical utility, necessitating the development of more selective agents. To overcome these challenges, personalized treatment approaches and combination therapies are being explored to improve treatment efficacy while minimizing adverse effects. Novel c-Met inhibitors with improved selectivity and reduced off-target toxicity show promise in preclinical studies. Additionally, targeted delivery systems aim to enhance drug localization and reduce systemic toxicity. Future directions involve refining inhibitor design and integrating c-Met inhibition into personalized treatment regimens guided by molecular profiling. This review explores the mechanisms by which c-Met contributes to chemoresistance in breast cancer and current challenges in targeting c-Met for breast cancer therapy. It discusses strategies to optimize treatment outcomes, ultimately improving patient prognosis and reducing mortality rates associated with this devastating disease.